Functional and taxonomic diversity of grasshoppers differentially shape above‐ and below‐ground communities and their function. (10th October 2020) - Lucas, Jane M.; Jonas, Jayne; Laws, Angela N.; Branson, David H.; Pennings, Steven C.; Prather, Chelse M.; Strickland, Michael S.
Abstract: Herbivores are important drivers in both above‐ and below‐ground ecosystems. Despite their importance, studies of herbivores often focus on the effects of individual species, potentially missing the effects of herbivore diversity. Here we examine how orthopteran herbivore species and functional (i.e. diet) diversity interact with nutrient availability to shape above‐ and below‐ground ecosystems. We stocked six species of grasshoppers (Orthoptera) with two different feeding modes (i.e. grass‐only or grass‐ and forb‐feeders) at varying taxonomic compositions (0, 1 or 6 species) in field enclosures and measured their effects on above‐ground plant biomass, chemistry and richness, as well as below‐ground microbial community composition and function. We treated half the cages with nitrogen fertilizer to examine how herbivore effects may be mitigated by soil nutrient availability. Above‐ground, we predicted that grasshoppers would decrease plant biomass and richness, and increase the %N of the plant community. We also predicted that high diversity cages would have the largest decreases in plant biomass and richness, but these effects would be offset by fertilizer additions. Below‐ground, we predicted that herbivore taxonomic composition and diet would differentially shift soil microbial community composition and function. We also predicted that fertilization would decrease the soil pH and increase nutrient availability creating an interaction with herbivores that leads to shifts below‐ground community composition. We found that grasshoppers decreased plant biomass and richness, and this effect was not dependent on nutrient additions. Contrary to our predictions, we did not see the largest above‐ground changes in high diversity cages. Below‐ground, herbivore diet and fertilization, but not their interaction, shifted bacterial communities. Grasshopper taxonomic composition did not influence bacterial communities. Grasshopper taxonomic composition and diet interacted with fertilizer to increase below‐ground levels of bioavailable C and microbial biomass. Fungal communities did not respond to any treatments. The differing effects of herbivore diet versus taxonomic composition highlight the need for studies that examine multiple diversity metrics when exploring herbivore‐meditated effects on above‐ and below‐ground ecosystems. Combined, our results suggest that bottom‐up and top‐down controls are important factors to consider when studying the composition and function of grassland ecosystems. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.